Domain-specific updating of metacognitive self-beliefs - Hoogervorst, Kelly; Banellis, Leah; Allen, Micah G. (Cognition, 2025)
Metacognitive self-monitoring is thought to be largely domain-general, with numerous prior studies providing evidence of a metacognitive g-factor. The observation of shared inter-individual variance across different measures of metacognition does not however preclude the possibility that some aspects may nevertheless be domain-specific. In particular, it is unknown the degree to which explicit metacognitive beliefs regarding one's own abilities may exhibit domain generality. Similarly, little is known about how such prior self-beliefs are maintained and updated in the face of new metacognitive experiences. In this study of 330 healthy individuals, we explored metacognitive belief updating across memory, visual, and general knowledge domains spanning nutritional and socioeconomic facts. We find that across all domains, participants strongly reduced their self-belief (i.e., expressed less confidence in their abilities) after completing a multi-domain metacognition test battery. Using psychological network and cross-correlation analyses, we further found that while metacognitive confidence exhibited strong domain generality, metacognitive belief updating was highly domain-specific, such that participants shifted their confidence specifically according to their performance on each domain. Overall, our findings suggest that metacognitive experiences prompt a shift in self-priors from a more general to a more specific focus.